PENGARUH PERSONAL COST, KOMITMEN ORGANISASI, SENSITIVITAS ETIS DAN MACHIAVELLIAN TERHADAP MINAT MELAKUKAN WHISTLEBLOWING (STUDI EMPIRIS PADA ANS DI OPD KOTA PEKANBARU) - Esther Oktavia; Rita Anugerah; Azhari Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to examine the influence of Personal Cost, Organizational Commitment, Ethical Sensitivity and Machiavellian To Whistleblowing Intention. This study was conducted at all OPD Pekanbaru City. The population in this study are all employees who work in OPD Pekanbaru City. The sampling method that used in this study is purposive sampling. Collecting data of this study using a questionnaire submitted to 70 employees who work on OPD Pekanbaru City. From questionnaires distributed, 54 questionnaires can be completed and can be processed. Data collected were analyzed with Stastistical Package fot the Sosial Sciences (SPSS).The results of hypotesis testing conclude that: first, personal cost has negative influence toward whistleblowing intention with value ???????????????????????? 2,706 > ???????????????????????? 1,67. Second, organizational commitment has negative influence toward whistleblowing intention with value ???????????????????????? 2,807 > ???????????????????????? 1,67. Third, Ethical Sensitivity has positive influence toward whistleblowing intention with value ???????????????????????? 4,029 > ???????????????????????? 1,67. Fourth, Machiavellian has positive influence toward whistleblowing intention with value ???????????????????????? 3,583 > ???????????????????????? 1,67 The result of the coefficient of determination (R2 ) is 0,520 wich means that the independent variable used in this research affects Whistleblowing Intention of 52,0% while the remaining 48,0% is influenced by other variables not included in this regression model.Keywords: Personal Cost, Organizational Commitment, Ethical Sensitivity, Machiavellian and Whistleblowing intention